2020
DOI: 10.1016/j.annonc.2020.08.1471
|View full text |Cite
|
Sign up to set email alerts
|

1824P Incidence, risk factors and clinical outcome of venous and arterial thromboembolism in patients treated with immune-checkpoint inhibitors

Abstract: q3w with an incidence ratio of 1.13 (0.19 e 4.70). Both groups had a high proportion of patients with low grade toxicity (fatigue, pruritus, rash; q6w 46%, q3w 42%). Table: 1821P Group characteristics (median, range) q6w q3w Age (yr) 72 (33-90) 72 (42-91) Follow-up time (months) 6.2 (0.1-11) 13.2 (2.5-44) Treatment cycles given 4 (1-10) 14 (3-57) Total treatment duration (patient-months) 391 1175.Conclusions: To our knowledge, this is the first analysis of toxicity data for a q6w Pembrolizumab regime. Incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In one secondary analysis within a prospective observational protocol of 217 NSCLC patients treated with checkpoint inhibitors, an elevated thrombosis incidence of 13.8% was noted (32). Other small, single institutional studies have also observed a correlation between checkpoint inhibitor therapy and thrombosis in cancer patients (33,34). In our study, we found a potential increased incidence of thromboembolic events among lung cancer patients who received first line checkpoint inhibitor monotherapy compared with chemotherapy either alone or combined with immunotherapy.…”
Section: Discussionmentioning
confidence: 97%
“…In one secondary analysis within a prospective observational protocol of 217 NSCLC patients treated with checkpoint inhibitors, an elevated thrombosis incidence of 13.8% was noted (32). Other small, single institutional studies have also observed a correlation between checkpoint inhibitor therapy and thrombosis in cancer patients (33,34). In our study, we found a potential increased incidence of thromboembolic events among lung cancer patients who received first line checkpoint inhibitor monotherapy compared with chemotherapy either alone or combined with immunotherapy.…”
Section: Discussionmentioning
confidence: 97%